PENGARUH VARIABEL EKONOMI MAKRO TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INONESIA - Yoelius Antonia Pujiharta; Haryoso Haryoso; Tri Widianto (ADVANCE, 2018)
The purpose of this research to provide empirical evidence to what extent inflation, foreign exchange rate, amount of money supply, Bank Indonesian Certificate Rate, and Gross Domestic Product toward Indonesian Composition Index IHSG at The Indonesian Stock Exchanges (IDX) for the period 2012-2016. Sample in the research is 60 sampel of monthly closing price data of independent and dependent variable.  The data used is secondary data with documentaton method. The sample technique used purposive sampling method. The analysis technique used in this research consists of classical assumption test in the form of normality test, multicolinearity test, heterokedasticity test, and autocorrelation test and hypothesis test in the form of multiple linear regression analysis, t test, F test, and R2 test. The result of reseacrh showed simultaniously inflation, foreign exchange rate, amount of money supply, Bank Indonesian Certificate Rate, and Gross Domestic Product have a significant effect toward Indonesian Composition Index IHSG, partially only Gross Domestic Product have a significant effect on the Indonesian Compisition Index IHSG. Coeficient of determination R2 is 0,37 or 37%. This mean that inflation, foreign exchange rate, amount of money supply, Bank Indonesian Certificate Rate, and Gross Domestic Produk are able to explain 37% of variable Indonesian Composition Index IHSG, while the remaining 63% is influenced by other variables not excamined.Keywords : inflatiton, foreign exchange rate, amount of money supply, Bank Indonesian certificate rate, Gross Domestic Product ,Indonesian Composition Index IHSG